69.4k views
5 votes
Find the inverse of the following. select all that apply ​

Find the inverse of the following. select all that apply ​-example-1
User Whitfiea
by
5.4k points

1 Answer

4 votes

Answer:


h^(- 1) (x) = \sqrt{(x - 8)^(3)} = (√(x - 8))^(3) = (x - 8)^{(3)/(2) }

Explanation:

The given function is
h(x) = \sqrt[3]{x^(2)} + 8 and we have to find the inverse function of this function h(x).

Now, let us assume,
y = \sqrt[3]{x^(2)} + 8


y - 8 = \sqrt[3]{x^(2)}


(y - 8)^(3) = x^(2) {Cubing both sides}

⇒ x² = (y - 8)³


x = \sqrt{(y - 8)^(3) }

Therefore, the inverse function
h^(- 1) (x) = \sqrt{(x - 8)^(3)} = (√(x - 8))^(3) = (x - 8)^{(3)/(2) }

So, options A, B, and D are correct. (Answer)

User Ricardo Anjos
by
5.7k points